The Chronicler's portrayal of Solomon as the King of Peace within the context of the international peace discourses of the Persian era - Jonker, Louis C. (Old Testament essays, 2008)
It has become customary to emphasise the influence of Greek historiography on the Books of Chronicles. Knoppers (2003a), for example, has argued that one should not underestimate the influence of classical Greek writers on the Chronicler. Although he argues his point from the genealogical analogies between the first part of Chronicles and classical writers, he convincingly shows that one could imagine Greek influence in biblical writings far earlier than the enigmatic date of 332 B.C.E., which is normally seen as a threshold for Greek influence on Judah. Traditional scholarship tended to interpret Chronicles exclusively within the cultic-religious conditions of the late-Persian / early Hellenistic province of Yehud - the Jerusalem community, in particular. With the acknowledgement of a wider sphere of influence during this time, it would make sense, however, to interpret the Books of Chronicles against the background of the international arena of the time. This article will therefore attempt to show that our understanding of King Solomon, the King of Peace, can be enriched when we view his portrayal in Chronicles within the international arena of the late post-exilic era. The theme of peace, so closely related to Solomon, will be examined against the background of the relationship between Greece and Persia, and the conditions within the Persian Empire.